Influence of thermal radiation on non-Darcian natural convection in a square cavity filled with fluid saturated porous medium of uniform porosity - Mahapatra, Tapas Ray Ray; Pal, Dulal; Mondal, Sabyasachi (Nonlinear Analysis: Modelling and Control, 2012)
Influence of thermal radiation on natural-convection flow in a square cavity filled with a porous medium of uniform porosity having isothermal vertical walls and adiabatic horizontal walls, has been studied numerically by using finite-difference method with staggered grid distribution. The simulation is performed by considering both Darcian and non-Darcian models. Governing momentum and energy equations are solved numerically to obtain velocity and temperature fields for various values of different physical parameters. It is seen that increasing the thermal radiation parameter enhances the local Nusselt number on the left vertical wall whereas the reverse effects are observed due to increase in the heat generating parameter when Ra = 109. The temperature at the mid-horizontal plane decreases with increase in the value of Rayleigh number up to a certain distance from the left vertical wall and beyond that distance the opposite trend is observed. The temperature at the mid-horizontal plane increases with increase in the value of heat generating parameter.